Hidden by the hair - a precocious puberty case report - Ferreira, Filipa A. (2020)
McCune-Albright syndrome (MAS) is one of the conditions causing precocious gonadotropin-independent puberty. It is a rare disease, characterized by two of the three following features: precocious puberty, polyostotic fibrous dysplasia (PFD), and café au lait (CAL) skin spots. Herein is presented the case of a girl with pubarche, acne, and transient thelarche since the age of three and menarche since the age of six years old. Besides transitory follicular cysts and advanced bone age, no other changes were found. Diagnosis was only established after brain magnetic resonance imaging showed fibrous dysplasia involving left craniofacial bones. The girl’s parents later mentioned that she had multiple café au lait skin spots on the scalp since birth, disclosing how the key diagnostic sign had been covered by the child’s hair. MAS is a rare disorder and diagnosis depends on a high index of suspicion. CAL skin spots are generally the first manifestation, but can easily go unnoticed. Additionally, PFD may only affect some bones, like craniofacial.